Semantics Analysis of Sentences, Utterances, and Presuppositions in Short Story: Two Kinds by Amy Tan - Aqilah Balqis Wardina; Hilma Safitri; Fildzah Zahirah; Jasmine Naya Shavia Chairunnisa; Riana Anggraini Bessi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research examines sentence utterance and presupposition, as represented in Amy Tan's short story "Two Kinds" (1989). Sentences are grammatically complete and are abstract. Utterance is the real embodiment of sentences. The presupposition is the assumption of hidden meaning. This research aims to understand how language structure, usage in real context, and implicit meaning interact in the communication process. The research method employed is a descriptive qualitative analysis of semantics. The results of this study indicate that the distinction between sentences and utterances is significant in analyzing semantic meaning. At the same time, presupposition can also reveal the point of view or language communication strategy. The theory used is from George Yule (1996) and Charles W. Kreidler (1998)